MODERN ASPECTS OF MEDICAL AND PHARMACEUTICAL AWARENESS OF HIV-INFECTED PATIENTS - Петров, Андрей Георгиевич; Хорошилова, Ольга Владимировна; Семенихин, Виктор Андреевич; Филимонов, Сергей Николаевич; Черных, Наталья Степановна (Medicine in Kuzbass, 2023)
According to the developed original questionnaire, which includes a number of blocks of questions, a medical and sociological study of HIV-infected patients was conducted. Statistical information included questions on such aspects as the patient: socio-demographic profile, awareness of the disease, satisfaction with the quality of medical care; and treatment: medical characteristics of the disease, characteristics of treatment, characteristics of pharmaceutical products. The aim of the study is to raise awareness of HIV-infected patients, aimed at health promotion and disease prevention. Material and methods. The object of research in the study of this problem are HIV-infected patients (n = 200). For this purpose, an original patient questionnaire has been developed for sociological research. The study was conducted using the method of expert assessments and their programmatic statistical processing in the Statistica 10 program. Results. Qualitative and quantitative facts have been revealed that allow us to conclude that there is insufficient awareness of HIV patients in a number of areas. The medical and sociological study of HIV patients allows medical and pharmaceutical workers to obtain, through feedback, an array of information on various aspects of medical and pharmaceutical care provided.